(untitled) (Web of Teachers: Inderscience Research, 2024)
In this article, we will discuss the role of Uzbek folk proverbs in preparing girls for family life. We examine how these proverbs shape attitudes, behaviors, and expectations about family relationships and provide girls with the tools to raise strong, loving, and cohesive families based on Uzbek cultural values and traditions. Through the age-old wisdom of folk proverbs, girls are guided to build a strong, supportive and nurturing family environment that supports the rich heritage of Uzbek culture.